Cariostatic Effect of Green Tea in Comparison with Common Anticariogenic Agents: An in Vitro Study - Mina Jazaeri; Farzaneh Pakdel; Loghman Rezaei-Soufi; Hamidreza Abdolsamadi; Nasrin Rafieian (Tabriz University of Medical Sciences, 2015)
Background and aims. Anticariogenic effects of different mouthrinses have been shown previously. In this in vitro study the anticariogenic effects of polyphenol extract of green tea with 0.05% fluoride, 0.2% chlorhexidine and fluoride-chlorhexidine were compared. Materials and methods. This in vitro study was performed on 50 maxillary premolars in 5 groups: 1) normal saline; 2) a 10% solution of green tea polyphenol extract; 3) 0.05% fluoride; 4) 0.2% chlorhexidine; and 5) fluoride-chlorhexidine. Each tooth was placed in a tube which contained a cariogenic solution. Every day the teeth were washed (depending on the ex-perimental groups) with 5 mL of mouthrinse solution. The depth of the caries was measured under a polarized light micro-scope. Data were analyzed using SPSS 13.0 with Kolmogorov-Smirnov, one-way ANOVA and Tukey tests. Results. The mean and standard deviation (in m) of caries depth were 194±16.43, 175±17.94, 142±9.34, 155±13.27, and 144±8.57 in groups 1 to 5, respectively, with significant differences between the groups (P<0.001). Tukey test showed that although there was no significant difference in the depth of caries in groups 1 and 2 (P>0.001), they were significantly less than those in groups 3 to 5 (P<0.001). There was no significant difference between decay depth of groups 3, 4 and 5 (P>0.001). Conclusion. The anticariogenic effect of fluoride-chlorhexidine was the highest among the groups. Although green tea showed higher cariostatic effects than normal saline, in comparison with other mouthrinses, it is less effective. More re-search is strongly recommended for clinical use of green tea as an anticariogenic agent.